Herb-drug interaction: Effect of aqueous extract of Bridelia ferruginea leaves on the pharmacokinetics of metformin - H. Brew-Daniels, A. A. Appiah, D. Edoh, M. M. Sakyiamah (Journal of Medicinal Herbs and Ethnomedicine, 2015)
The concurrent use of herbal medicines and orthodox drugs, especially in the treatment and management of chronic ailments, may result in clinically significant herb-drug interactions. Bridelia ferruginea Benth (Euphorbiaceae) is a common medicinal plant with known anti-diabetic properties and has been reported to be taken alongside the orthodox medicine, metformin. The aim of this study was to investigate the effect of aqueous extract of B. ferruginea leaves on the pharmacokinetics of metformin in female Sprague-Dawley rats. Reconstituted freeze dried extract of B. ferruginea leaves (30 mg/kg), and metformin (7 mg/kg) were administered concurrently as a single dose to female Sprague-Dawley rats. Whole blood samples (1 ml) were aseptically withdrawn by tail bleeding at 1, 2, 4, 8, and 24 h after administration of the single dose for pharmacokinetics analyses. Concurrent administration of metformin and B. ferruginea significantly affected (P < 0.05) all the pharmacokinetics parameters of metformin except for the time to attain the maximum concentration (Tmax), which increased but insignificantly. Whereas the area under the curve, maximum whole blood concentration (Cmax) and half-life (TÂ½) of metformin decreased significantly in the presence of B. ferruginea, the elimination rate constant (Kel), clearance (Cl), absorption rate constant (Ka), and volume of distribution (Vd) of metformin increased significantly in the presence of B. ferruginea. Therefore, in clinical practice, patients should be advised on the implication of concurrent administration of metformin and B. ferrruginea.